VOLATILITAS HARGA SUSU SAPI DAN SUSU KAMBING SERTA DAMPAKNYA DALAM PROGRAM PENCEGAHAN STUNTING DI KECAMATAN KARANGPAWITAN - Firmansyah, Rian; Rahayu Putra, Rizky; Muhammad Fiqri, Desta; Murwenie, Ira (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2025)
This study aims to analyze the price volatility of cow's milk and goat's milk on the elasticity of consumer demand in Karangpawitan District in an effort to prevent stunting. The research method used was descriptive quantitative with data collection techniques carried out by purposive random sampling in Karangpawitan District. The data obtained were analyzed using simple linear regression analysis to identify the relationship between the variables studied. The results showed that cow's milk price volatility was able to explain the significant impact on stunting prevention by 89% and goat's milk price volatility was able to explain the significant impact on stunting prevention by 98.4%. In addition, cross-elasticity analysis showed a complementary relationship between the two types of milk (-1.17). Therefore, it is recommended to implement a milk price subsidy policy and strengthen nutrition education to reduce stunting.